Pineapple Princess - Hahn, Sabina (New York : Roaring Brook Press, 2022)
A misunderstood girl, who is certain she is a princess, creates a pineapple headpiece fit for royalty--unfortunately, a horde of eager subjects in the form of flies take direction poorly and her kingdom slowly devolves into chaos, causing both her rule and her pineapple crown to fall apart.
new kids book 2022 summer.
Ages 4-8.
Grades K-1.
Keywords: Play -- Fiction; Imagination -- Fiction; Picture books